Effects of Thematic-Based Instruction on Students' Academic Achievement and Attitudes Towards English Course - Gökhan Baş; Ömer Beyhan (Mehmet Tekerek, 2012)
The purpose of the study was to examine the effects of thematic-based instruction on elementary students' academic achievement and attitudes towards English course. The research was carried out in 2011-2012 education-instruction year in an elementary school in Niğde province. Totally 60 students in two different classes in the 6th grade of this school participated in the study. The pre/post-test control group quasi-experimental research model was used in this study. In order to test the significance between the groups, the independent samples t test was adopted in the study. The results of the research showed a significant difference amongst academic achievement and attitudes towards course in favor of the experimental group.